The Influence of Youth Perceptions in Prambatan Village on Interest in Business in the Agricultural Sector Using Structural Equation Modeling (SEM) Methods - Hardina, Tri; Nugroho, Tri Wahyu; Toiba, Hery (SERUNAI, 2023)
Youth tend not to be interested in the agricultural sector. This study aimed to determine the perceptions that influence the interest of rural youth in the agricultural sector. This research was conducted using a quantitative approach and was conducted in Prambatan Village, Balen Sub-district, Bojonegoro Regency. The determination of informants was carried out using random sampling method and 70 youth in Prambatan Village were obtained as informants. Data analysis was conducted using the Structural Equation Modeling (SEM) method. The result was that there were three perceptions that significantly influence the interest of youth in Prambatan Village to do business in the agricultural sector, namely social perceptions (X2), psychology (X3), and convenience (X4). Meanwhile, economic perceptions (X1) and benefits (X5) had T statistics less than 1.96 and P values greater than 0.05. So for X1 and X5, Ho was accepted and H1 was rejected so that it was stated that it had no effect.